An integrated model to evaluate land rent - Emília Maria Malcata Rebelo (2003)
The main theme of this paper, which is based upon a research that is being developed at the Faculty of Engineering of Porto University, consists in the theoretical definition and the practical implementation of a mass appraisal evaluation system for land rents in urban sites where urban interventions/developments in the high tertiary sector are expected. This model is applied, as a case study, to the Porto city (Portugal).The assessment and methodology proposed consists in the establishment of an interactive and integrated model that relates the levels of land rent where office buildings bear on, to the price levels of the offices themselves, considering the inter-dependencies between both property markets.The potentiality of this model consists in its appropriateness to local realities, in the definition of an evaluation model using computational tools to deal with updated networked information, and in in its flexibility to adapt to different realities/explanatory factors. This model leads to the development of a set of urban management tools that reinforce municipal decisions, and its cartographic interface through Geographic Information Systems allows the simulation of alternative courses of municipal action.It is, thus, proposed the reinforcement of the planning and municipal power agentsŽ role in property markets, through the adjustment of fiscal tools to urban realities, the avoidance of speculation procedures, and the warrant of the social appropriation of (at least part of) the surplus values that accrue from the initiatives of public administration .